Analysis of Structural Strength at the Stern with the Addition of Stern Roller on TB ASL Prosper VI Ship - Andrianto Andrianto; Agung Prasetyo Utomo; Luqman Cahyono (Department of Naval Architecture - Diponegoro University, 2026)
This study analyzes the structural strength of the stern of the TB. ASL PROSPER VI vessel after the addition of a stern roller, a vital component for anchor handling that significantly affects load distribution. The analysis was carried out under three loading scenarios: (1) static load with the anchor resting on the roller, (2) dynamic load during anchor lifting, and (3) extreme load according to ABS classification rules. The stern roller was modeled in 3D and analyzed using the finite element method (FEM), with validation performed through manual calculations. The results show that the designed stern roller has a total weight of approximately 3 tons. Under static conditions, the maximum stress was 2.35 MPa on the roller and 1.33 MPa on the stiffener, with a deflection of 0.69 mm and safety factors of 15.21 and 17.96, respectively, indicating a very safe condition. In the anchor lifting scenario, the stress increased to 12.45 MPa (roller) and 10.10 MPa (stiffener), with a deflection of 1.4 mm and safety factors of 12.05 (roller) and 14.98 (stiffener), which are still within safe operational limits. However, under the extreme ABS load case, the stress reached 110.74 MPa on the roller and 391.88 MPa on the stiffener, resulting in safety factors of 1.35 and 0.38, respectively, indicating structural failure in the stiffener. It can be concluded that the stern roller is structurally safe for normal operations and anchor handling, but reinforcement is required to ensure compliance with ABS standards under maximum load conditions.